Possible simplified method for the determination of the resilient modulus of unbound granular materials. Issue 4 (1st October 2016) - Thach Nguyen, Bao; Mohajerani, Abbas
Abstract : The behaviour of flexible pavements is commonly characterised by the resilient modulus, which can be determined from the repeated load triaxial test in the laboratory. The repeated load triaxial testing standard varies from one organisation to another and can take up to 15 hours to complete. This paper presents the results of a possible simplified testing method, which may significantly reduce the testing time to 4.5 hours. The differences between the resilient modulus values from the standard testing method and those from the proposed simplified testing method are found to be insignificant for the 14 different experimental unbound granular materials.